IMPLEMETASI MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MENULIS CERPEN PADA SISWA KELAS XI SMAN 2 MENGWI - Ni Putu Ritha Anggadewi; Dewa Gede Bambang Erawan; Ni Wayan Eminda Sari (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research is a Classroom Action Research (PTK) which aims (1) Mengimplementation of the project based learning learning model to increase the activity and learning outcomes of short story writing for class XI students of SMAN 2 Mengwi; and (2) describe the steps for implementing the project based learning learning model to increase the activity and learning outcomes of short story writing in class XI students of SMAN 2 Mengwi. The subjects of this study were 38 class XI students of SMAN 2 Mengwi. Methods of data collection in the form of observation, documentation, and collection of student work. The data collection instruments used were observation sheets and tests. The learning outcomes of students' short story writing increased after the second cycle was carried out. In the first cycle, students' short story writing learning outcomes increased with a classical mastery percentage of 21% in the low category. In cycle II, the percentage of students' classical short story writing learning outcomes experienced 79% so that it became 100% and was in very high criteria. So it can be concluded that the implementation of the Project Based Learning learning model can improve the learning outcomes of writing short stories for class XI SMAN 2 Mengwi.